Pharmacodynamic effect of dipyridamole on thallium-201 myocardial perfusion in progressive systemic sclerosis with diffuse scleroderma. Issue 9 (September 1986) - Kahan, A; Devaux, J Y; Amor, B; Menkes, C J; Weber, S; Foult, J M; Venot, A; Guerin, F; Degeorges, M; Roucayrol, J C
Abstract : We evaluated the effect of dipyridamole on thallium-201 myocardial perfusion in 23 patients with progressive systemic sclerosis (PSS) with diffuse scleroderma. Thallium-201 single photon emission computed tomography (SPECT) was performed at rest and after coronary artery vasodilatation with intravenous dipyridamole (0.14 mg/kg/min for four minutes). The left myocardium was divided into nine segments; each segment was graded as 2.0, 1.5, 1.0, 0.5, 0 (zero represents no activity). Dipyridamole significantly improved resting thallium-201 myocardial perfusion: the mean (SD) number of segments with thallium defects decreased from 6.0 (2.1) at rest to 4.1 (2.5) after dipyridamole (p less than 0.0001); the mean (SD) score in segments with resting defects increased from 0.92 (0.24) at rest to 1.13 (0.38) after dipyridamole (p less than 0.0001); the mean (SD) global score per patient increased from 10.2 (1.8) at rest to 11.4 (2.1) after dipyridamole (p less than 0.02); the global score increased by at least 2.0 in 12 patients and worsened by at least 2.0 in three patients only (p = 0.05). The results of this acute study suggest that some drugs with potent vasodilator activity on small coronary arteries may be beneficial in the treatment of PSS patients with thallium-201 myocardial perfusion abnormalities.